Revisiting the size-effect in mergers and acquisitions : four decades of evidence on the underperformance of large firms - Forgó, Zoltán (2024)
The underperformance of large acquirers compared to smaller ones is well documented in literature. In this study I examine the value-creation of 22,588 acquisitions in the US between 1980 and 2023. I find on average a positive, 0.86% abnormal return for all bidders; however, when considering value-weighted returns, the same average portrays a much more striking value-destruction of -0.45%. I also document a net of 262 billion dollars of aggregate market capitalization being wiped out due to acquisitions in the past four decades. My dissertation corroborates the findings of previous studies on the existence of the so-called size-effect. I find a significant, -1.08% difference between the returns of large and small acquirers on announcement. This difference cannot be explained by a wide range of variables used for predicting bidder returns in literature, including target size. My results are also robust to choices made in the research design and hold up to a high statistical standard.